Pengembangan Jamur Tiram Menjadi Produk Masker Wajah dengan Automaticfacial Mask Machine - Indayani; Sitti Hajar; Wahyu Lestari (Jurnal Mitra Pengabdian Farmasi, 2022)
One form of Usaha Mikro Kecil dan Menengah (UMKM) is the oyster mushroom production business. Oyster mushroom (Pleurotus ostreatus) is rich in protein, minerals and vitamins so it is beneficial for health. This oyster mushroom can be developed into various products. The purpose of this community service is to increase the income of entrepreneurs and traders of oyster mushrooms in Limpok Village, Darussalam District, Aceh Besar. Through this community service, it is hoped that new products will be created with the basic ingredients of oyster mushrooms. The antioxidant content of oyster mushrooms will be tested using the DPPH method. The result of this community service is the latest innovation from oyster mushroom products in the form of face masks.